Protection System Analysis of 20 kV Medium Voltage Distribution Network: A Case Study on SM3 Feeder, Tomohon Main Substation - Amelia Oktavianty Palit; Marcela Beatrix Karewur; Brayen Aprilio Pijoh; Samsu Tuwongkesong; Donald Bastian Noya (Jurnal Impresi Indonesia, 2026)
The protection system of a 20 kV medium-voltage distribution network plays a critical role in ensuring the reliability and safety of power delivery. An effective protection system must rapidly and selectively detect and isolate faults to minimize the affected area and outage duration. The SM3 Feeder at the Tomohon Main Substation, operated by PT PLN (Persero) UP3 Manado, serves a region characterized by diverse network configurations and environmental conditions, requiring a robust and well-coordinated protection scheme. This study analyzed the performance of the protection system on the SM3 Feeder, employing a methodology that encompasses collection of technical data for installed protection devices including circuit breakers (PMT), automatic reclosers, fuse cut outs (FCO), and protection relays. The analysis evaluates the coordination and settings of these devices against the fault characteristics of the network and benchmarks them against PLN and IEC standards. In addition, an IoT-based monitoring and protection system was designed and tested to complement conventional field protection. Results indicate that the protection system on SM3 Feeder generally functions adequately in safeguarding the network. However, certain conditions require adjustment particularly the coordination margin between the main relay and Recloser RC-1 at fault currents between 500–700 A. Improved coordination is expected to reduce the extent of affected areas during faults and enhance overall supply reliability. This study serves as an evaluation basis and provides actionable recommendations for PLN in managing and improving the medium-voltage distribution protection system in the UP3 Manado service area.